A completely self-contained cryogen-free dilution refrigerator, the TritonDRTM: Техника свеpхнизких темпеpатуp - Mikheev, V.A.; Noonan, P.G.; Adams, A.J.; Bateman, R.W.; Foster, T.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Oxford Instruments have developed a new dilution refrigerator for ultralow temperatures down to below 35 mK. The TritonDRTM system is a continuous cryogenic cycle dilution refrigerator. The refrigerator is driven by a closed cycle cryocooler and hence requires no liquid cryogens. The system has a dedicated electronic control unit and software that provides full control of operation.